UAP Values Reflected in Selected COVID-19 Themed Digital Literature for Children and Young Adults - Catharina Brameswari; Almira Ghassani Shabrina Romala; Nathaniel Alvino Risa Prima; Theresia Enny Anggraini (Universitas Sanata Dharma, 2023)
Digital Literature for Children and Young Adults (LCYA) reveals children and young adults’ experiences in the real world from their perspectives. It also portrays that most children and young adults face complex and enormous challenges in this digital world to find their true selves, potentials, and future, particularly during this COVID-19 pandemic. The goal of this LCYA is in line with Jesuit’s Universal Apostolic Preferences (UAP), which “commit to promoting a healthy and safe environment for children and young people so that they can develop their full potential as human beings.” Therefore, this research scrutinizes Universal Apostolic Preferences (UAP) values reflected in selected COVID-19-themed Digital Literature for Children and Young Adults (LCYA). Importantly, Digital Literature is a Garden of Eden for digital natives, Gen-Z, and digital readers where they can access literary texts from their smartphones, tablet, and laptop. These issues are essential to be discussed because children and young adults are the future generations, the future world, and future humanity. This pandemic should be seen from a different perspective, for this condition has encouraged us to take care of ourselves and others, especially children and young adults. Importantly, those digital works are also reminders that children’s and young adults’ energy and spirit can bring love and changes to our planet. This research attempts to develop our empathy in understanding the loneliness, misery, and suffering of others during this difficult time. Digital Literature and Literature for Children and Young Adults (LCYA) discourses are suitable for use since this research uses digital short stories highlighting children and young adults’ lives during the COVID-19 pandemic.